Pengaruh Kualitas Penerapan Good Corporate Governance dan Risiko Pembiayaan terhadap Profitabilitas Perbankan Syariah - Ferly Ferdyant; Ratna Anggraini ZR; Erika Takidah (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2014)
The purpose of this research is to analyze the influence of the quality of the implementation of good corporate governance toward profitability of Islamic Banks and analyze the influence of non performing finance toward profitability of Islamic Banks. This research used secondary data from financial statements published by Bank Indonesia and Annual Report GCG in 2010-2013. The Techniques used for sampling is purposive sampling and obtained by 10 Islamic Banks with a total sample of 39 Islamic Banks. Profitability ( Dependent Variable ) in this research is proxied by Return on Assets ( ROA) .While the Independent Variable is The Quality Implementation of Good Corporate Governance obtained from Composite GCG Self Assessment Report Annual Islamic Banking, and Financing Risks are proxied by the Non -Performing Finance ( NPF ). The influence of the three variables and relationships are tested using multiple regression analysis. T-test SPSS results showed that the quality of the implementation of Good Corporate Governance has negative influence and significant toward profitability of Islamic banking. Non-Performing Finance has negative influence and significant toward profitability of Islamic banking. While the F-test SPSS results showed Implementation of Good Corporate Governance and Quality of Non-Performing Finance has negative influence and significant toward profitability of Islamic banking. Thus, this hypothesis is proven.The purpose of this research is to analyze the influence of the quality of the implementation of good corporate governance toward profitability of Islamic Banks and analyze the influence of non performing finance toward profitability of Islamic Banks. This research used secondary data from financial statements published by Bank Indonesia and Annual Report GCG in 2010-2013. The Techniques used for sampling is purposive sampling and obtained by 10 Islamic Banks with a total sample of 39 Islamic Banks. Profitability ( Dependent Variable ) in this research is proxied by Return on Assets ( ROA) .While the Independent Variable is The Quality Implementation of Good Corporate Governance obtained from Composite GCG Self Assessment Report Annual Islamic Banking, and Financing Risks are proxied by the Non -Performing Finance ( NPF ). The influence of the three variables and relationships are tested using multiple regression analysis. T-test SPSS results showed that the quality of the implementation of Good Corporate Governance has negative influence and significant toward profitability of Islamic banking. Non-Performing Finance has negative influence and significant toward profitability of Islamic banking. While the F-test SPSS results showed Implementation of Good Corporate Governance and Quality of Non-Performing Finance has negative influence and significant toward profitability of Islamic banking. Thus, this hypothesis is proven.